Cooperative empowerment towards democratization and economic development The case of Sts. Peter and Paul Multi-Purpose Cooperative in Hinunangan, Southern Leyte. - Arquion, Julie Pearl P. (Julie Pearl P. Arquion, 2009)
Cooperatives play a vital role in fostering development and democratization. Through the services rendered by the cooperatives it is of much evidence that they help uplift the socio-economic status of the people. The purpose of this study is to know and assess the capability of the Sts. Peter and Paul Multi-Purpose Cooperative to promote development as well as adhered to the principles of democratization. The following variables were utilized: strategies for capital buildup, membership and public participation, marketing strategies, and managerial performance and formation of political alliances. I engaged myself into interviewing some of the officials and members with regards to their experiences with the Cooperative. This study examines how democratization works in the SPPMPC based on the abovementioned variables. Results from these suggest that the SPPMPC toil to forward development and foster democratization among its members and to the Cooperative.